“It is all her fault”: psychosocial correlates of the negative attitudes towards rape victims among the general population of Pakistan - Syed Messum Ali Kazmi; Rabia Iftikhar; Muhammad Umar Fayyaz (Egyptian Journal of Forensic Sciences, 2023)
Abstract Background Rape myths are marked for being false beliefs about sexual assault. With the problem being quite prevalent around the world, research has shown that numerous factors such as rape proclivity and perpetuation of rape myths are critical. The present study assesses the role of rape myths acceptance, rape victim empathy, and causal attributions towards rape victims as significantly predicting attitudes towards rape victims among the general population of Pakistan. Rape myths acceptance and causal attributions would significantly and positively predict negative attitudes towards rape victims. Method A cross-sectional research design was used for the study. The online survey questionnaire was filled by 573 participants including 275 males and 298 females who were selected through purposive sampling from the general population of Pakistan. The sample size was estimated using G*Power analysis with 95% confidence intervals. Data collection was done using Illinois rape myths, attitudes towards rape victim’s scale, rape victim empathy, and causal attributions scale were used. Data analysis was done using Pearson product-moment correlation, hierarchical regression, MANOVA, and mediation analysis via AMOS, all of which were executed using SPSS 21.0. Results The findings showed that higher levels of rape myths acceptance, low empathy towards rape victims, and victim blaming are significantly associated with negative attitudes towards rape victims. There were no gender differences among the participants. However, rape victim empathy significantly mediated the association between rape myths acceptance and rape victim empathy. It was also found that rape myths acceptance, rape victim empathy, and causal attributions significantly predicted attitudes towards rape victims. Another core finding was that there were no gender differences among participants with regard to rape myths acceptance, rape victim empathy, causal attributions, and attitudes towards rape victims. Conclusions Therefore, the findings contribute towards a better understanding of the rape myths in the general population of Pakistan and how the prevalence of such myths may contribute towards social, cultural, and legal problems of rape myths. The study also provides policy implications for a region where rape victims experience higher levels of blame and limited legal backing and support.